Guidance and Counseling Strategies to Overcome Game Addiction in Students as an Effort to Support Social Change - Nasution, Salsabila; Firman; s, Neviyarni (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2024)
Game addiction among Indonesian students are increasing increase and cause impact significant to performance academics, mental health, and interactions social. Research This aiming for explore role Guidance and Counseling (BK) in handle game addiction in students, as well as identify strategies that can applied for reduce problem this. Based on the data obtained from the Padang City Education Office, around 25% of students at the elementary school level school intermediate first and top experience game addiction with duration more from four hours per day, which is related with decline performance academic, disturbance sleep, and improvement anxiety. Research This use approach qualitative with studies literature for analyze the role of BK in give intervention through various strategies, such as counseling. Findings show that interventions involving​ assessment beginning, approach based on motivation, and support social from parents and schools​ can help student overcome game addiction and increase quality life they. Research this also emphasizes importance involvement together between BK, parents, and school in create supportive environment​ change positive on students. It is hoped that the results study This can give outlook for practitioner education in design a more program effective for overcome game addiction among student.